TINDAKAN MANIPULATIF JASA ANIMAL COMMUNICATOR DI ERA MODERN: TINJAUAN KOMPARATIF PERLINDUNGAN KONSUMEN DI INDONESIA DAN SINGAPURA - Christy; Shenti Agustini; Nurlaily (Fakultas Hukum Universitas Kristen Indonesia, 2026)
Animal communicator services in Indonesia raise legal issues because they are prone to manipulation and difficult to verify. Consumers are often harmed by exaggerated claims, misleading information, and the absence of clear compensation mechanisms. This study aims to identify and compare consumer protection in Indonesia and Singapore, as well as analyze regulatory weaknesses in Indonesia in order to formulate policy recommendations. Using normative juridical methods and a comparative legal approach, this study analyzes the urgency of reconstructing consumer protection using responsive law theory by Philippe Nonet and Philip Selznick. The results show that the principle of freedom of contract can be abused to legitimize fraudulent practices, while consumers' rights to information, safety, choice, and compensation are often violated. Furthermore, overlapping regulations, such as the provisions between the UUPK and PP PMSE, weaken legal certainty. Therefore, legal reconstruction is necessary through more responsive regulations, strengthening dispute resolution institutions, and establishing transparency standards for service providers.